Pengaruh Kredit Macet, Tingkat Efisiensi dan Likuiditas Terhadap Profitabilitas: Studi pada Perbankan Umum Konvensional yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Julianti Eka Putri; Nor Norisanti; Sopyan Saori (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study was to determine how the influence of Bad Debt, Efficiency Level and Liquidity on Profitability both partially and simultaneously. The data used in this study are secondary data in the form of financial statement data on conventional public banking companies listed on the Indonesia Stock Exchange for the period 2020-2022. The research methods used are descriptive and associative methods with a quantitative approach. The sampling technique used in this study used a non-probability sampling approach with purposive sampling method. The data analysis techniques used are multiple correlation coefficient test, coefficient of determination, multiple linear regression test, partial test (t test) and simultaneous test (f test). Based on the results of the study, it shows that from the partial test (t test) Bad Credit (NPL) shows a result of 0.294 where tcount 1.065 < t table 2.024 with a significance value of 0.294, then the Efficiency Level shows a result of 0.000 where tcount 22.440 < t table 2.024 with a significance value of 0. 000, then Liquidity shows a result of 0.002 where tcount 3.396 < ttable 2.024 with a significance value of 0.002. the conclusion is that Bad Debt partially has no effect on Profitability while the Efficiency Level, Liquidity partially has an effect on Profitability.